DETERMINANTS OF ADOPTION OF AGRICULTURAL INNOVATIONS AND PROFITABILITY OF CEREALS AND LEGUMES IN THE SUDAN SAVANNA OF NIGERIA - AYANWALE, A.B.; ABDOULAYE, T.; KAMARA, A. Y.; ADEKUNLE, A.; FATUNBI, O.; AYEDUN, B.; AKINOLA, A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
In order to facilitate a scientific assessment of the viability of the IAR4D concept, this paper analyzed the factors affecting adoption of agricultural technologies as well as determined  the profitability  of cereals  and legumes  in  the  Sudan  savanna  of Nigeria. Data were obtained from the baseline study conducted in 2008 as well as other official secondary data. Descriptive statistics, budgetary as well as logistic regression techniques were used to analyze the data. Results show that the respondent's age range vary between 40 and 55 years implying that they are relatively  young  elders  with  large family size of between  12 and  14 possibly providing family labour for farm work. The educational level is expectedly low with only about a third of them having up to six years of formal   education.   The   regression   results reveal that the location of the farmer, large family size and awareness encouraged adoption of new technologies across the various sites. The gross margin analysis reveals that among the cereal  crops, maize gave the highest yield and revenue, while for legume  crops,  groundnut  gave  the  highest yield  and revenue  figures  in all sites  with labour being the highest variable cost item on all sites. In conclusion, the study affirmed that farmers in the study area possess the potential to adopt agricultural innovations which could increase yields and enhanced income